Analysis of the Current State of Population Growth and Level of Vehicle Ownership (Texas Journal of Engineering and Technology, 2022)
As a result of the growth and development of the world's population, the needs of each person are increasing more and more. For example, in the 1980s, the average need of a person was 80, by the 2000s, this indicator increased to 200, and by now it is more than 400. This indicates the development of humanity. Also, the level of automobileization is increasing year by year. These indicators, on the one hand, ease the problem of humanity, on the other hand, they cause great damage to the environment. This article analyzes population growth and carization rates over the years